Fluoride removal by thermally treated egg shells with high adsorption capacity, low cost, and easy acquisition - Lee, Jae In; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Environmental Science and Pollution Research, 2021)
In this study, the use of eggshells was suggested as an adsorbent for fluoride removal, and their mechanism of fluoride removal was investigated. The eggshells underwent thermal treatment to improve their adsorption capacity; 800 °C was found to be the optimal temperature for treatment. Eggshells thermally treated at 800 °C (ES-800) were mainly composed of Ca (82.4%) and C (15.9%), and the peaks of ES-800 obtained from X-ray diffraction (XRD) corresponded to calcite, portlandite, and lime. Fluorine adsorption by ES-800 reached 70% of the equilibrium adsorption amount within 15 min and gradually increased until 24 h. The maximum adsorption capacity of ES-800 at pH 7 and 25 °C was 258.28 mg/g, which is 18 times larger than that of activated alumina; this is classified as the best available technology by the United States Environmental Protection Agency. Both enthalpy and entropy increased in the process of fluoride adsorption onto ES-800. Fluoride adsorption of ES-800 decreased from 59.16 to 11.85 mg/g with an increase in pH from 3 to 11. Fluoride adsorption decreased in the presence of anions, whose impact follows the order: HPO43− > HCO3− >> SO42− > Cl−. XRD, and X-ray photoelectron spectroscopy analysis revealed that fluoride removal was achieved by the formation of calcium fluorite (CaF2). Thus, it can be concluded that eggshells can function as highly efficient adsorbents for fluoride removal, replacing bone char and activated alumina; further, their adsorption capacity can be improved by thermal treatment.
Keywords: Adsorption; Animals; Egg Shell; Fluorides; Hydrogen-Ion Concentration; Kinetics; Water Pollutants, Chemical; Water Purification; Adsorption; Characterization; Eggshell; Fluoride; Removal; Thermal treatment